Blair's successful war British military intervention in Sierra Leone - Dorman, Andrew M. 1966- (Military strategy and operational art, 2009)
Andrew Dorman introduces Sierra Leone as Blair's second great military adventure after Kosovo and the first he undertook on his own. The book links Blair's move toward humanitarianism with the rise of cosmopolitan militaries and the increasing involvement of Western forces in humanitarian operations and their impact on the international system, and will prove to be a key reader on the topic.